COMPARATIVE BEHAVIORAL STUDY BETWEEN JUVENILE AND ADULT Rumina decollata (MOLLUSCA, SUBULINIDAE) - Souza, Fabíola Almeida Matos de; Pilate, Vinícius José; Chicarino, Evelyn Durço; Ribeiro, Luana Cortez; Silva, Lidiane Cristina da; Bessa, Elisabeth Cristina de Almeida (Revista Nordestina de Zoologia, 2013)
Land snails are largely utilized all over the world in several sectors of economy. However, there is a lack of studies about behavioral displays of alien species in the areas of introduction. The aim of the present work was to verify the activity period and the behavioral displays exhibited by individuals of Rumina decollata (Linnaeus, 1758). It was utilized 30 young and 30 adult snails, observed during 24 hours by the method scan sample at intervals of 20 minutes. It was verified that this snail species presents nocturnal activity and adults were more active than young individuals. The behavioral display “Interact” showed significantly difference during the 24 hours of observation, with more interaction between adults. It was observed difference in the act “Feed” between young and adult snails in two hours during the scotophase (21 and at 3 hours) and in the act “Dislocate” at 21, 23 and 3 hours. The relative air humidity did not influence the snail’s behavior, but there was a positive correlation between the mean temperature and the activity of adult snails. The results demonstrated that R. decollata presents activity and rest period alike to other Subulinidae and showed difference in some behavioral displays between juvenile and adult snails, what can be attributed to niche differentiation in order to avoid intraspecific competition. Besides, because this species remains buried most of the time, it cannot be effective in controlling other snail species.